Environmental Management Policy Analysis in the Context of Sustainable Development - Geanisha, Merlin; Depari, Ruth Anastasya (IHSA Institute, 2025)
This research examines environmental management policies within the framework of sustainable development, aiming to assess their effectiveness and implications for future practices. Through a comprehensive analysis of case studies from diverse geographical contexts, the study identifies key elements that contribute to successful environmental governance, including robust regulatory frameworks, active stakeholder engagement, and the integration of economic considerations with environmental objectives. The findings reveal that effective policies are characterized by inclusivity and adaptability, allowing for flexibility in response to emerging environmental challenges. Additionally, the research highlights the critical role of technology in enhancing monitoring and participation, empowering communities, and fostering accountability in policy implementation. By reinforcing the interconnectedness of environmental health and socio-economic progress, this study advocates for holistic approaches that align local actions with global sustainability goals. The insights generated from this analysis contribute to the ongoing discourse on sustainable development, offering a roadmap for policymakers to design and implement more effective environmental management strategies that promote resilience, equity, and stewardship in the face of pressing ecological challenges.